Differential Fertilization and Nutritive Substrates Effect on the Flowering Degree of Pelargonium Zonale - TOMOŞ, Camelia; MĂRGHITAŞ, Marilena (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca. Agriculture, 2013)
This paper presents researches regarding the effect of differential fertilization and nutritive substrates on the flowering degree of Pelargonium zonale species. Aim of this subject research resulted from the desire to conduct experiments that provide results with beneficial impact on geraniums crop, results allowing production of some quality plants, both in terms of aesthetics and plant health.Research followed the effect of differential fertilization and of nutritive substrates on the degree of geraniums flowering. The research focused on experiments designed to highlight favourable combinations of soil and fertilizer for geraniums development and particularly, favourable for flowering (the main ornamental quality). The types of substrate, fertilizers, pH varies depending on the type of crop, the substrate and the source of fertilizer and can be affected by the source of water and the type of irrigation system. Relative acidity or alkalinity of the substrate type affects directly the availability of nutrients in the plants root system. By applying the fertilizers, amendments and culture technology can be changed, to a large extent, the direction of the chemical and biochemical process from soil as well as the fertility status.